An integrative approach to uncover the components, mechanisms, and functions of traditional Chinese medicine prescriptions on male infertility - Bai, Xue; Liu, Zhejun; Tang, Tian; Yu, Shujun; Liu, Dan; Liu, Guimin; Fan, Xiaolei; Tang, Yibo; Liu, Zhenquan (Frontiers in Pharmacology, 2022)
Male infertility is a major and growing health problem with an estimated global prevalence of 4.2%. The current therapy is limited by the unknown etiology of MI, emphasizing the critical requirement forward to a more efficient method or medication. Through thousands of years, Traditional Chinese Medicine (TCM) has been shown to be effective in treating MI effectively. However, the components, mechanisms and functions of TCM prescriptions on MI are still obscure, severely limiting its clinical application. In order to discover the molecular mechanism of TCM against MI, our study presents a comprehensive approach integrated data mining, network pharmacology, molecular docking, UHPLC-Q-Orbitrap HRMS, and experimental validation. Here, we begin to acquire 289 clinical TCM prescriptions for MI from a TCM hospital's outpatient department. Then, Core Chinese Materia Medica (CCMM) was then retrieved from the TCM Inheritance Support System (TCMISS), which was utilized to discover the underlying rules and connections in clinical prescriptions. After that, 98 CCMM components and 816 MI targets were obtained from ten distinct databases. Additionally, the network pharmacology methods, including network construction, GO and KEGG pathway enrichment, PPI analysis, were utilized to reveal that kaempferol, quercetin, isorhamnetin, and beta-sitosterol are the core components of CCMM in treating MI. The mechanisms and functions of CCMM against MI are hormone regulation, anti-apoptosis, anti-oxidant stress, and anti-inflammatory. Furthermore, the strong connections between four core components and six key targets were verified using a molecular docking method. Following that, the core components of the CCMM extract were identified using UHPLC-Q-Orbitrap HRMS analysis. Finally, in vivo experiments demonstrated that CCMM and four core components could improve the density, motility, viability of sperm, lecithin corpuscle density, decrease the rate of sperm malformation and testis tissue damage, and regulate the protein expressions of AKT1, MAPK3/1, EGFR, TNF-α in a mouse model of MI. UHPLC-Q-Orbitrap HRMS analysis and in vivo experiments further validated the results of data mining, network pharmacology, and molecular docking. Our study could uncover the components, mechanisms, and functions of TCM prescriptions against MI and develop a new integrative approach to demonstrate TCM's multi-component, multi-target, and multi-pathway approach to disease treatment.